FOLFIRI-bevacizumab and concurrent low-dose radiotherapy in metastatic colorectal cancer: preliminary results of a phase I–II study. (December 2014) - Morganti, Alessio G.; Mignogna, Samantha; Caravatta, Luciana; Deodato, Francesco; Macchia, Gabriella; Plantamura, Nunzio M.; Massaccesi, Mariangela; Picardi, Vincenzo; Cilla, Savino; Valentini, Vincenzo
<x content-type="archive" xml:space="preserve">Abstract</x> Background: To evaluate the effectiveness of low-dose radiation therapy (LDRT) and FOLFIRI-bevacizumab (FOLFIRI-B) combination in metastatic colorectal cancer. Methods: The primary objective of the study is to raise the clinical complete response (CR) rate from 5% to 25%. Secondary objectives include toxicity and progression-free survival. Patients underwent 12 FOLFIRI-B cycles plus two daily LDRT (20 cGy/6-hour interval) on the first and second days of each cycle. Results: CR and toxicity of 10 patients are reported. Considering irradiated sites, 10/10 patients had clinical partial response (PR) (7/10) or CR (3/10). Three clinical PR patients subsequently underwent surgery and reported a pathological CR in the irradiated sites. Grade 3–4 toxicities rate was 30%. With a median follow-up of 29 months (range: 12–49 months), 2/10 progression of disease in irradiated sites and 3/5 in non-irradiated sites were observed. Conclusions: The very high response rate requires urgent verification in a larger patient series.